The Effect of Financial Market Depth on Economic Growth in Developing Countries with Large Financial Sectors - Mabeba, Mahlatse (Social Science Studies, 2024)
The financial market depth has emerged as a phenomenon shaping developing economies with large financial sectors. This paper presents the effect of financial market depth on economic growth in developing countries with large financial sectors from 1996 to 2022. While developing countries are typically characterized by lower levels of economic development and industrialization, some of them may have relatively large financial sectors. These countries include Brazil, India, Indonesia, Malaysia, Mexico, and South Africa. We utilize the random effects model, a panel data econometrics model, to estimate the nexus. Our proxy for financial market depth is the stock market capitalization as percentage of gross domestic product. A higher market capitalization suggests larger and more liquid markets. The indicator of economic growth is the real gross domestic product, which is growth accounted for inflation. We find that financial market depth has a significant and positive effect on economic growth in developing countries with large financial sectors. The novelty of the study is that the financial market depth and economic growth nexus is significantly moderated by financial and trade openness.